Efektivitas Penerapan Video YouTube dan Google Form dalam Pembelajaran PAI di SMAN 2 Kota Sukabumi - Cecep Hilman (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
Referring to preventive measures to overcome the spread of Covid-19 in schools, the application of distance learning (Online) must be implemented so that all educators are required to use technology-based learning. The use of Information and Communication Technology (ICT) in learning Islamic Religious Education (PAI) in accordance with the 2013 curriculum can be a variety of media and media that can be used as a reference are YouTube and Google Form. This research is a descriptive qualitative research-based research conducted at SMAN 2 Sukabumi City. The results of this study found that YouTube-based learning media is more effective than Google Form in Islamic Religious Education Learning (PAI). From the results of the questionnaire, it can be seen that the Google Form media is more suitable as a medium for evaluating students than as the main medium for learning.